WELL CASING STRENGTH INTEGRITY ANALYSIS DUE TO SUBSIDENCE - SARWONO (NIM : 13103062); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, EKO
The need of oil and natural gas as primary energy sources continues to increase today. Many Efforts for exploration, exploitation, production and distribution are improved to meet the needs of oil and natural gas. But in the process have a major obstacle caused by geohazard, one of which is with the occurrence of subsidence. This Final Project performs casing strength integrity analysis in oil and gas well affected by subsidence in LIMA area of Java Sea. The analysis is conducted to determine casing stress distribution due to subsidence using Finite Element software Nastran for Windows 4.5 to ensure its reliability. The results of linear stress analysis of LA - 9ST well shows that the highest stress is at a depth of 2,234 ft with a maximum stress 476,370 psi. Maximum stress occurs at the 9-5/8 inch casing has a yield strength of 80,000 psi and 95,000 psi ultimate strength. It is necessary to perform non-linear stress analysis because the linear stress analysis results exceed the yield strength and ultimate strength casing material. The nonlinear stress analysis results of LA - 9ST well shows that the highest stress is at a depth of 2,234 ft with 92,016 psi maximum stress and 6.17% maximum strain.